Development of Student Book as a Means to Instill Social Care, Honesty, and Responsibility to Enhance Academic Achievement in Elementary School - Putri, Helena Anggraeni; Siswanto, Deny Hadi; Suryatama, Handika (International Journal of Learning Reformation in Elementary Education, 2025)
This study aims to explore the development of a student book designed to instill the values of social care, honesty, and responsibility in third-grade students at Muhammadiyah Ambarbinangun Elementary School. The student book is intended to meet validity, practicality, and effectiveness criteria to enhance students' academic achievement. The research method used was Research and Development with the ADDIE model, involving 30 students as subjects. Data were collected through observation and testing. The results showed that media expert validation yielded a score of 4.5, categorized as very valid, while material expert validation received a score of 4.2, also categorized as very valid. Based on student questionnaires, the average response score reached 4.3, categorized as very practical. The average posttest score of students reached 78,2, compared to a pretest score of only 55,4. Paired sample testing showed a significance level below α (0.00 < 0.05), indicating a significant difference in student achievement before and after using the student book. The N-Gain score obtained was 0.51, classified as moderate.